Gene expression patterns induced by human rhinovirus species B infection using an In Vitro model of human type II alveolar pulmonary epithelial cell line - Etemadi, Mohammadreza (2016)
Human rhinoviruses (HRVs) belong to the family Picornaviridae are the most commonly isolated viruses in acute respiratory infections. It has been associated with exacerbations of lower respiratory tract infections especially among individuals with chronic respiratory disease such as chronic obstructive pulmonary disease (COPD) and asthma by induction of inflammation through perturbation in airway epithelial cells. Achieving a suitable treatment which can target both virus replication as well as inflammatory response is feasible through better understanding of the virus-cell interactions and host cell response to the infection. Although the differences between HRV species A/B/C have been presented in terms of clinical manifestations and disease prevalence, the experimental data is rather controversial regarding to HRV species B which may be clinically relevant and beneficial as drug targets. Genomewide transcriptional analysis using microarray technology was used to understand whether human lung epithelial cells infected with HRV species B is associated with specific gene expression pattern at different time points after infection using an in vitro system. HRV-B72 (ATCC® VR-1182™) was propagated in H1HeLa cells and subsequently concentrated by ultracentrifugation and purified through sucrose gradient. Then the virus titer was determined using plaque assay. Human lung alveolar epithelial cell line (A549) was used for subsequent infection and gene expression analysis. Cell viability was measured using both thiazolyl blue tetrazolium bromide (MTT) assay. Total RNA was extracted from HRV-infected and mock-infected cell monolayers at 6, 12, 24 and 48 hpi in three independent replicates. The transcriptional profiles of epithelial cells infected with HRV-B72 was analyzed using high-density oligonucleotide Affymetrix GeneChip ®PrimeView Functional categories enriched in differentially expressed genes at each time points were analyzed by DAVID bioinformatics resources. At the end of the current study, representative genes from different functional groups were selected for validation study using qRT-PCR assay. The data acquired from experiments analyzing both intracellular and extracellular viral RNA level demonstrated significant replication of the HRV-B72 which further supports the in vitro proof for implicating of rhinovirus in lower airway epithelium. In total 991 genes were found differentially expressed during the course of infection. Of these, 459 genes were up-regulated whereas 532 genes were down-regulated. Differential gene expression at 6 hpi (184 genes up-regulated vs. 156 down-regulated) were significantly represented by gene ontologies related to the chemokines and inflammatory molecules indicating characteristic of viral infection. The 75 upregulated genes surpassed the down-regulated genes (35) at 12 hpi and their enriched ontologies fell into discrete functional entities such as regulation of apoptosis, antiapoptosis, and wound healing. At later time points of 24 and 48 hpi, predominated down-regulated genes were enriched for extracellular matrix proteins and airway remodeling events. Selected differentially expressed genes (DEGs) form diverse gene ontologies (CXCL8, CCl20, CXCL3, BCL2A1, FOSL1, JUN, EGR1 and DUSP6) showed consistent trend in RT-qPCR assay. Our data provides a comprehensive image of host response to HRV-B72 infection using in vitro system. Profound gene expression modifications was observed in the context of pronounced virus propagation suggesting that HRV-B72 is potentially able to infect alveolar epithelial cells and induce cell transcriptional perturbations. HRVB72 induced expression of CXC and CC chemokines. Uncontrolled expression of the chemokines can eventually lead to pathological inflammatory reactions. The study suggests the underlying molecular regulatory networks genes which might be involved in pathogenicity of the HRV-B72 and potential targets for further validations and development of effective treatment.